2002
DOI: 10.1081/rrs-120014603
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Proximity Assay, a Novel Method for Exploring Peptide Ligand–receptor Interaction

Abstract: Probing G-protein coupled receptor (GPCR) structures is a priority in the functional and structural understanding of GPCRs. In the past, we have used several approaches around photoaffinity labeling in order to establish contact points between peptide ligands and their cognate receptors. Such contact points are helpful to build reality based molecular models of GPCRs and to elucidate their activation mechanisms. Most studies of peptidergic GPCRs have been done with photolabeling peptides containing the benzoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 27 publications
1
45
1
Order By: Relevance
“…A bias for recovery of peptide fragments from these TM segments was not observed for unmodified peptide fragments. The propensity of benzophenone-type photoligands to react with methionine residues (Rihakova et al, 2002) is reflected by the fact that highest labeling is observed in methionine-containing sequences Gln169-Met170 in TM3, Leu268-Met269-Ile270 in TM5, and Met295-Met296-Tyr297 in TM6.…”
Section: Resultsmentioning
confidence: 99%
“…A bias for recovery of peptide fragments from these TM segments was not observed for unmodified peptide fragments. The propensity of benzophenone-type photoligands to react with methionine residues (Rihakova et al, 2002) is reflected by the fact that highest labeling is observed in methionine-containing sequences Gln169-Met170 in TM3, Leu268-Met269-Ile270 in TM5, and Met295-Met296-Tyr297 in TM6.…”
Section: Resultsmentioning
confidence: 99%
“…Benzophenonetype ligands have initially been reported to be nonselective (Dorman and Prestwich, 2000). A preferred reaction with methionine residues in proteins has been reported (Rihakova et al, 2002;Wahlstrom et al, 2002). Methionine residues in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1c) (21,(23)(24)(25). In the FIGURE 1. a, MPA (59). Following the binding of the Bpa-substituted ligand with its target, the benzophenone group of the Bpa photoprobe is photoactivated at 350 -360 nm to generate a reactive triplet biradical ketone intermediate (19).…”
Section: Methodsmentioning
confidence: 99%